Histone H2A-Reactive B Cells Are Functionally Anergic in Healthy Mice With Potential to Provide Humoral Protection Against HIV-1 - Agazio, Amanda; Cimons, Jennifer; Shotts, Kristin M.; Guo, Kejun; Santiago, Mario L.; Pelanda, Roberta; Torres, Raul M. (Frontiers in Immunology, 2020)
Peripheral tolerance is essential for silencing weakly autoreactive B cells that have escaped central tolerance, but it is unclear why these potentially pathogenic B cells are retained rather than being eliminated entirely. Release from peripheral tolerance restraint can occur under certain circumstances (i.e. strong TLR stimulus), that are present during infection. In this regard, we hypothesized that autoreactive B cells could function as a reserve population that can be activated to contribute to the humoral immune response, particularly with pathogens, such as HIV-1, that exploit immune tolerance to avoid host defense. In this study, we identify a population of autoreactive B cells with the potential to neutralize HIV-1 and experimentally release them from the functional restrictions of peripheral tolerance. We have previously identified murine monoclonal antibodies that displayed autoreactivity against histone H2A and neutralized HIV-1 in vitro. Here, we identify additional H2A-reactive IgM monoclonal antibodies and demonstrate that they are both autoreactive and polyreactive with self and foreign antigens and are able to neutralize multiple clades of tier 2 HIV-1. Flow cytometric analysis of H2A-reactive B cells in naïve wildtype mice revealed that these B cells are present in peripheral B cell populations and we further document that murine H2A-reactive B cells are restrained by tolerance mechanisms. Specifically, H2A-reactive B cells display increased usage of Ig lambda light chain, suggesting previous central B cell tolerance censoring by receptor editing, and fail to mobilize calcium upon immunoreceptor stimulation, a marker of anergy. Moreover, we show that toll-like receptor stimulation or provision of CD4 T cell help induces the in vitro production of H2A-reactive antibodies, breaking tolerance. Thus, we have identified a novel poly/autoreactive B cell population that has the potential to neutralize HIV-1 but is silenced by immune tolerance.